Security and Privacy in Cloud Computing: Challenges and Opportunities - Ballamudi, Venkata Koteswara Rao; Desamsetti, Harshith (American Journal of Trade and Policy, 2017)
ICT advancements have made cloud computing popular and successful. Cloud computing lets corporate users relocate and utilize the pay-as-you-go price model’s scalability. However, outsourcing data and business applications to the Cloud or a third party creates security and privacy concerns, which are crucial to cloud adoption. Researchers and impacted organizations have offered several security measures to address security issues in the literature. Cloud computing security and privacy are extensively covered in the literature. Unfortunately, literature efforts lack flexibility in mitigating numerous threats without contradicting cloud security aims. The literature has also focused on security and privacy issues and has yet to give technical solutions. Research on technical remedies to security concerns has yet to explain their origins. This paper introduces security and privacy challenges that require adaptive solutions without compromising cloud security. This research evaluates the literature, including its adaptability to future threats and how cloud security conflicts have invalidated their models. The essay uses STRIDE to highlight cloud computing security issues from a user perspective. It also analyses literature-based inefficient solutions and recommends secure, adaptive cloud environments.